Human Health Risk Associated with As, Cu, Pb, and Zn in Soils of the Aconcagua and Casablanca River Basins, Valparaíso Region, Chile - Jaume Bech; Daniela Pradenas; Pedro Tume; Óscar Cornejo; Javiera Pedreros; Sofía Toledo; Claudio Correa; Bernardo Sepúlveda; Núria Roca (Applied Sciences)
Chile is an important producer of copper, and it has serious soil contamination problems, mainly related to mining activities. A typical example is the Aconcagua River basin, which has been the scene of large-scale mining operations throughout history, making it critical to analyze due to the high concentrations of heavy metals in its soils. The objectives of this study are (1) to assess the level of As, Cu, Pb, and Zn contamination in the surface soil ecosystem based on different environmental indexes and (2) to determine the health risks of adults and children located in watersheds of the Aconcagua and Casablanca Rivers. A database of the Aconcagua River and Casablanca River basins is used to achieve the objectives. From the Aconcagua River basin, 20 topsoil samples from agricultural sectors without mining activity and 127 topsoil samples from sectors with mining activity were selected. On the other hand, thirty-five topsoil samples of the Casablanca River basin, without mining activity, were analyzed. The evaluation of soil contamination was done using environmental indexes. Finally, carcinogenic and noncarcinogenic risks to humans were calculated using the USEPA model. The mean concentration of chemical elements in the Aconcagua River basin for samples without mining presence was As 10.55 mg kg−1, Cu 85.75 mg kg−1, Pb 26.65 mg kg−1, and Zn 139.5 mg kg−1. The correlations show that the elements As, Cu, Pb, and Zn come from anthropogenic sources, which are also enhanced by the geogenic origin of Cu and Zn. The spatial distribution of the analyzed elements shows a spatial pattern that extends across industrial areas and emission sources, with higher concentrations of As, Cu, Pb, and Zn identified near mining areas of the Aconcagua River basin. The upper limit of the geogenic values determined by the MAD (median absolute deviation) method for the Aconcagua River basin without mining presence was 14.5 mg kg−1 for As, 94 mg kg−1 for Cu, 37.5 mg kg−1 for Pb, and 194 mg kg−1 for Zn. Finally, the geoaccumulation index, contamination factor, integrated contamination index, and potential ecological risk registered exceptionally high contamination in some soil samples, especially in areas with mining influence. It is essential to highlight that there are non-carcinogenic risks related to As, Cu, and Pb, a hazard quotient (HQ) higher than 1, and acceptable carcinogenic risks between 1.0 × 10−6 and 1.0 × 10−4 to As and Pb in children and adults in the Aconcagua River basin.